The Algerian Constitutional Council between dependency and independence in light Constitutional Amendment 2016 - HASSAINE, Samia; HACENE ASSAFRA, Hamed Mahmoud (Journal of Human Sciences, 2020)
The control of the constitutionality of laws is one of the basic pillars of the protection of the principle of the supremacy of the Constitution. The mechanisms of moving this censorship differ from state to state according to the type of censorship adopted in the state constitution between political supervision and judicial supervision. The task of this oversight in Algeria and in accordance with the Algerian constitution is the Constitutional Council, which raises the question of its independence and subordination in view of the executive authority, although this Council of importance in the study of the system of government in general is of importance in what was under the conditions experienced by Algeria and in this period of completion Custody and turnout in presidential elections.